Insulin-Like Growth Factor 2 mRNA Binding Protein 3 Promotes Cell Proliferation of Malignant Mesothelioma Cells by Downregulating p27Kip1 - Endo, Ihiro; Amatya, Vishwa Jeet; Kushitani, Kei; Kambara, Takahiro; Nakagiri, Tetsuya; Fujii, Yutaro; Takeshima, Yukio (Frontiers in Oncology, 2022)
Malignant mesothelioma is a tumor with a poor prognosis, mainly caused by asbestos exposure and with no adequate treatment yet. To develop future therapeutic targets, we analyzed the microarray dataset GSE 29370 of malignant mesothelioma and reactive mesothelial hyperplasia, downloaded from the Gene Expression Omnibus (GEO) database. We identified insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3) as one of the significantly upregulated genes in malignant mesothelioma. IGF2BP3 functions as an oncoprotein in many human cancers; however, to our knowledge, this is the first study on the biological function of IGF2BP3 in malignant mesothelioma cells. The knockdown of IGF2BP3 in malignant mesothelioma cells resulted in the suppression of cell proliferation with an increase in the proportion of cells in the G1 phase of the cell cycle. Furthermore, knockdown of IGF2BP3 inhibited cell migration and invasion. We focused on the cell cycle assay to investigate the role of IGF2BP3 in cell proliferation in malignant mesothelioma. Among the various proteins involved in cell cycle regulation, the expression of p27 Kip1 (p27) increased significantly upon IGF2BP3 knockdown. Next, p27 siRNA was added to suppress the increased expression of p27. The results showed that p27 knockdown attenuated the effects of IGF2BP3 knockdown on cell proliferation and G1 phase arrest. In conclusion, we found that IGF2BP3 promotes cell proliferation, a critical step in tumorigenesis, by suppressing the expression of p27 in malignant mesothelioma.